Rejection of Application for Registration of Trademark Payfazz Agen Keuangan Nusantara Based on Law Number 20 Year 2016: Penolakan Permohonan Pendaftaran Merek Dagang Payfazz Agen Keuangan Nusantara Berdasarkan Undang-Undang Nomor 20 Tahun 2016 - Herdi Agriansyah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The principle of trademark registration in Indonesia is first to file, i.e. who first registers his trademark is considered as the owner or holder of rights to the trademark. Trademark registration should not be based on bad faith, because in Law Number 20 of 2016 concerning Trademarks and Geographical Indications, the application for trademark registration must be rejected. The purpose of this study is to determine the refusal of the application for registration of the Payfazz Agen Keuangan Nusantara trademark based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Decision Number 25/Pdt.Sus-Merek/2020/Pn.Niaga.Jkt.Pst and to determine the legal consequences of the refusal of the application for registration of the Payfazz Agen Keuangan Nusantara trademark based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Decision Number 25/Pdt.Sus-Merek/2020/Pn.Niaga.Jkt.Pst. This research uses a normative juridical approach method with analytical descriptive research specifications. The data collection method is done by literature study, the data obtained is presented with narrative text, and the data analysis method used is qualitative normative method. The results of the research can be concluded that the refusal of the application for registration of the mark “PAYFAZZ AGENT FINANCIAL OBLIGATIONS NUSANTARA‘’ which was rejected by the Defendant was appropriate in accordance with the provisions of Article 21 paragraph (1) letter b of Law Number 20 of 2016 concerning Trademarks and Geographical Indications and the legal consequences of the refusal of registration of the mark ‘PAYFAZZ AGENT FINANCIAL OBLIGATIONS NUSANTARA’' is that the Plaintiff has lost the right, interests, and benefits under the law arising from the Trademark ''PAYFAZZ OBLIGATORY FINANCIAL AGENT NUSANTARA'', and has suffered immaterial losses because the problems with the registration of the Trademark ''PAYFAZZ OBLIGATORY FINANCIAL AGENT NUSANTARA'' took up a lot of time, costs, energy, and thoughts of the Plaintiff, because the Defendant erred in applying the applicable law.